A manifest nodoventricular accessory pathway with unusual electrophysiological manifestations. Issue 5 (18th July 2022) - Li, Jun; Liu, Qifang; Yang, Long
Abstract : A nodoventricular accessory pathway showing the degree of anterograde decremental conduction was more than the atrioventricular node.